A 9‐Year Prospective Case Series Using Multivariate Analyses to Identify Predictors of Early and Late Peri‐Implant Bone Loss. (3rd July 2014) - Vervaeke, Stijn; Collaert, Bruno; Cosyn, Jan; De Bruyn, Hugo
Abstract: Purpose: The study aims to identify predictors of early and late peri‐implant bone loss following complete implant‐supported rehabilitation using multivariate analyses. Materials and Methods: Fifty patients (28 women, 22 men; mean age 58, range 35–76) in need of a complete implant‐supported rehabilitation on five to eight implants were consecutively treated. Patients were reinvited for a clinical and radiographic examination after an average 9 years of function. Implant survival and peri‐implant bone loss were considered the dependent variables. Multivariate analyses were adopted to identify predictors of early and late peri‐implant bone loss. Results: In total, 39 patients were examinated. Two implants failed after 4 years of function, resulting in an overall survival rate of 99.2%. After a mean follow‐up of 9 years, mean bone loss of 1.68 mm (SD 2.08, range −1.05 to 10.95) was found. The abutment height was a significant predictor of early peri‐implant bone loss (1 year) ( p = .024), whereas smoking ( p = .046) and history of periodontitis ( p = .046) affected late peri‐implant bone loss. Conclusion: Within the limits of this study, it can be concluded that initial bone remodeling was affected by soft tissue thickness as reflected by the height of the abutment, whereas smoking and history of periodontitis affected long‐term peri‐implant bone stability.